2005
DOI: 10.1158/0008-5472.can-04-3334
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanism-Based Antioxidant Approach for the Reduction of Skin Carcinogenesis

Abstract: Studies in our laboratories showed that overexpression of manganese superoxide dismutase (MnSOD) reduced tumor incidence in a multistage skin carcinogenesis mouse model. However, reduction of MnSOD by heterozygous knockout of the MnSOD gene (MnSOD KO) did not lead to an increase in tumor incidence, because a reduction of MnSOD enhanced both cell proliferation and apoptosis. The present study extends our previous studies in the MnSOD KO mice and shows that apoptosis in mouse epidermis occurred prior to cell pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
130
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(135 citation statements)
references
References 16 publications
5
130
0
Order By: Relevance
“…Our further synthetic efforts in searching for a potential therapeutic based on the SAR led us to Mn(III) ortho N-alkylpyridylporphyrins as the most potent candidates for forwarding them into animal models where superoxide-mediated damage is involved. Thus remarkable effects were observed in cancer, radiation, diabetes, ALS, Alzheimer's disease etc [13][14][15][16][17][18][19][20][21][22][23]. Further, along with our mechanistic studies we observed a dramatic impact of the positive charges of the Mn porphyrin on the O 2 •− dismutation; the rate constants are more than two orders of magnitude higher when compared to the neutral or negatively charged porphyrins [3,4].…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Our further synthetic efforts in searching for a potential therapeutic based on the SAR led us to Mn(III) ortho N-alkylpyridylporphyrins as the most potent candidates for forwarding them into animal models where superoxide-mediated damage is involved. Thus remarkable effects were observed in cancer, radiation, diabetes, ALS, Alzheimer's disease etc [13][14][15][16][17][18][19][20][21][22][23]. Further, along with our mechanistic studies we observed a dramatic impact of the positive charges of the Mn porphyrin on the O 2 •− dismutation; the rate constants are more than two orders of magnitude higher when compared to the neutral or negatively charged porphyrins [3,4].…”
Section: Introductionsupporting
confidence: 57%
“…In all previous studies the data obtained with E. coli parallel the trends obtained in in vivo animal model studies [1][2][3][4][5][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]37]. Here we compare the effect of Mn II Br 8 TM-3-PyP 4+ , its metal-free porphyrin HBr 8 TM-3-PyP 3+ , and the para analogue Mn II Br 8 TM-4-PyP 4+ on the aerobic growth of an SOD-deficient E. coli strain.…”
Section: Protection Of Aerobic Growth Of Sod-deficient E Colimentioning
confidence: 64%
“…It became obvious that the effects observed when using Mn porphyrins were not only the consequence of mere scavenging of ROS=RNS, but that MnPs were also able to modulate ROS=RNS-based signaling pathways. Several articles that followed provided evidence that a potent SOD mimic= ONOO À scavenger, such as MnTE-2-PyP 5þ , can strongly inhibit excessive activation of redox-sensitive cellular transcriptional activity (39,221,222,259,288,322,350).…”
Section: A Metalloporphyrinsmentioning
confidence: 99%
“…Inhibition of redox-controlled cellular transcriptional activity. Mn(III) N-alkylpyridylporphyrins inhibit in vitro and in vivo activation of several redox-controlled transcription factors (TFs), HIF-1a, NF-kB, AP-1, and SP-1 (158,221,222,288,322,350). Although not studied yet, such action may occur with other redox-controlled TFs.…”
Section: Reactivity Towardmentioning
confidence: 99%
See 1 more Smart Citation